Complementary description and record of Neocyclops ferrarii (Cyclopidae: Halicyclopinae) from northern Colombia (2017)
The interstitial cyclopoid copepod Neocyclops ferrarii Rocha, 1995 was found in samples obtained from littoral areas of Rodadero Bay, northern Colombia. The specimens from Colombia share the diagnostic features of N. ferrarii presented in the original description. However, the Colombian specimens show some degree of variation with respect to the type material in: 1) the number of teeth in the labrum; 2) the length of outer exopodal spine on female leg 5; 3) the relative length of the mandibular palp setae; 4) length/width ratio of caudal rami; 5) the length ratio of caudal setae VI/III; 6)  the length ratio of caudal setae VII/VI; 7) the male body size; 8) the male caudal rami length/width ratio; 9)  This is the second record of this species after its original description from Belizean waters. In the Caribbean region N. ferrarii most closely resembles N. vicinus Herbst, both of them bear an antennary exopod, a 12-segmented female antennule, P3ENP3 armature formula 3,III, but can be  separated from the latter by difference in the length/width ratio of the female caudal ramus, the length ratio of caudal setae VI/III, the length ratio of caudal setae VII/VI, the male body size, the number of segment of P4ENP, the armature details of mandibular palp and the number of segments of male P5.  This is the second species of Neocyclops recorded from Colombia and represents a distributional range expansion of N. ferrarii in the Caribbean Basin.